"At night he cries from dreams": Perceptions of children's psychological distress and wellbeing amongst parents with refugee or asylum seeker backgrounds in Australia. (6th August 2019) - Due, Clemence; de Heer, Nathaniel; Baak, Melanie; Hanson‐Easey, Scott
Abstract : Objective: The objective of the current study was to gain insight into the ways in which parents who had arrived in Australia with refugee or asylum seeker backgrounds understand their young children's experiences of wellbeing and psychological distress during resettlement. Method: Eight parents (three male and five female) who had arrived in Australia from Iran and Afghanistan with children aged between five and eight were recruited using purposive sampling. In‐depth interviews were conducted regarding their perceptions of their children's experiences of wellbeing and psychological distress. Thematic analysis was used to analyse the data. Results: Four primary themes were developed: (a) Practical needs are a key priority, (b) the refugee experience impacts family structure and dynamics, which has a negative effect on children's wellbeing, (c) wellbeing as engagement in physical activity and education, and (d) bad dreams and difficulty sleeping are indicators of psychological distress. Conclusions: For parents recently arrived in Australia as refugees or asylum seekers, practical concerns impact perceptions of children's wellbeing or psychological distress, particularly for those on temporary visas. While this may lead parents to overlook symptoms of psychological distress in their children, protective factors conducive to wellbeing, including safety, housing, and education, are prioritised. Future research should explore when and why parents are likely to seek assistance for their children in the context of resettlement, as well as the impacts of visa types on children's experiences of positive wellbeing and psychological distress.